Studi Literatur: Implementasi Model Pembelajaran Kooperatif Terhadap Peningkatan Hasil Belajar Kognitif Siswa Pada Materi Biologi - Ainullatiffah, Noor; Mulyono, Yatin (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2024)
The success of the learning process cannot be separated from the teacher's ability to apply creative and innovative learning models in order to provide stimulus to students to be more active in the learning process. The teacher-centered teaching and learning process has an impact on students not having learning motivation and has an impact on low student learning outcomes. This study aims to determine the improvement of student learning outcomes on biological material by applying a cooperative learning model. The method used in this study is a literature study by analyzing and identifying related scientific articles so as to produce a more informative, objective and reliable summary. Data collection in this study through jurals indexed by Scopus and Google Scholar. The results showed that the application of the cooperative learning model was effectively used in improving student learning outcomes.